Multiscale anode materials in lithium ion batteries by combining micro- with nanoparticles: design of mesoporous TiO2 microfibers@nitrogen doped carbon composites. Issue 33 (29th July 2015) - Cheng, Wei; Rechberger, Felix; Primc, Darinka; Niederberger, Markus
Abstract : We designed mesoporous micron sized fibers composed of TiO2 nanocrystals and coated with N doped carbon with excellent electrochemical performance. Abstract : TiO2 has been considered as a promising anode material for lithium ion batteries. However, its poor rate capability originating from the intrinsically low lithium ion diffusivity and its poor electronic conductivity hampers putting such an application into practice. Both issues can be addressed by nanostructure engineering and conductive surface coating. Herein, we report a template-assisted synthesis of micron sized TiO2 fibers consisting of a mesoporous network of anatase nanoparticles of about 7.5 nm and coated by N doped carbon. In a first step, an amorphous layer of TiO2 was deposited on cobalt silicate nanobelts and subsequently transformed into crystalline anatase nanoparticles by hydrothermal treatment. The N doped carbon coating was realized by in situ polymerization of dopamine on the crystalline TiO2 followed by annealing under N2 . After removal of the template, we obtained the final mesoporous TiO2 fibers@N doped carbon composite. Electrochemical tests revealed that the composite electrode exhibited excellent electrochemical properties in terms of specific capacity, rate performance and long term stability.